Effect of ethanol fumigation on CNSL oil and diesel blends. Issue 7 (19th May 2021) - Govindan, S.; Thangaraj, M.; Rajeshkumar, M.; Logesh, K.
ABSTRACT: In this work, preheated CNSL oil and diesel blends with ethanol fumigation were tested for a one-cylinder compression ignition engine to determine the engine efficiency and emission level under different load conditions at a constant speed. First, an experiment was conducted for preheated CNSL oil at different temperatures, i.e. 70° C, 80° C and 90° C. The optimized preheated temperature of 80° C was selected based on the engine performance and emissions. The various blends are such as [(Preheated CNSL20 + D80) +E fumigation], [(Preheated CNSL40 + D60) +E fumigation], [(Preheated CNSL60 + D40) +E fumigation, (Preheated CNSL80 + D20) +E fumigation], [(Preheated CNSL100) +E fumigation] were tested in the engine at optimized temperature (80° C). The results are compared with that of pure diesel fuel. The engine efficiency and emissions are improved in the blends of [(preheated CNSL20 + D80) +E fumigation] at optimized temperature.